2010
DOI: 10.1088/0031-9120/45/4/011
|View full text |Cite
|
Sign up to set email alerts
|

A datalogger demonstration of electromagnetic induction with a falling, oscillating and swinging magnet

Abstract: We investigate the electromagnetic induction phenomenon for a falling, oscillating and swinging magnet and a coil, with the help of a datalogger. For each situation, we discuss the salient aspects of the phenomenon, with the aid of diagrams, and relate the motion of the magnet to its mathematical and graphical representations. Using various representation modes to guide student thinking on how the variation of the magnetic flux can be used to predict the induced electromotive force should help students develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…There has been various studies on the phenomenon of electromagnetic induction with sensors such as the classic example of a magnet falling through a coil [4], where the acceleration due to gravity can be calculated [5]. Other experiments involved magnets moving at constant speed through a coil, swinging as a magnetic pendulum over a coil, and oscillating in a coil [6][7][8]. This paper probes deeper into the emf induced in a coil due to an oscillating bar magnet along the coil's axis as the amplitude of oscillation was varied.…”
Section: Introductionmentioning
confidence: 99%
“…There has been various studies on the phenomenon of electromagnetic induction with sensors such as the classic example of a magnet falling through a coil [4], where the acceleration due to gravity can be calculated [5]. Other experiments involved magnets moving at constant speed through a coil, swinging as a magnetic pendulum over a coil, and oscillating in a coil [6][7][8]. This paper probes deeper into the emf induced in a coil due to an oscillating bar magnet along the coil's axis as the amplitude of oscillation was varied.…”
Section: Introductionmentioning
confidence: 99%
“…Most of them deal with pulses induced by a magnet falling through a coil or inside a conductive pipe [1][2][3][4][5][6][7][8]. Many experiments related to the electromagnetic induction law using harmonic oscillation have been reported; however, they are limited to analyzing the time variation of the magnetic flux by integrating the waveform data of the induced voltage [9]. Many studies have suggested experimental devices and application methods for the analysis of electromagnetic induction phenomena [10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Some authors looked at the connections between the magnet and coil relative velocity and the induced signal shape, amplitude and width. Others discussed different signal acquisition methods [3][4][5][6][10][11][12][13][14][15]. Applications, for example measuring the speed of a magnet passing through a coil were discussed [2,4,7].…”
Section: Introductionmentioning
confidence: 99%